2021
DOI: 10.1002/jcla.24066
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA MIR4435‐2HG functions as a ceRNA against miR‐125a‐5p and promotes neuroglioma development by upregulating TAZ

Abstract: Glioma is the most common primary central nervous system tumor, accounting for more than half of all primary intracranial tumors. 1 According to the World Health Organization (WHO) classification scheme, gliomas can be divided into four types: mixed glioma, neuroepithelial tumor, gliomatosis cerebri, and neuroglioma. 2 The transcription coactivator TAZ, which contains 400 amino acids, is one of the most important downstream effectors of the mammalian Hippo pathway. Its structure consists of a transcriptional-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Additionally, it has been confirmed through research that MIR4435-2HG has the ability to activate the Wnt/β-catenin signaling pathway by suppressing the expression of desmoplakin (DSP), thus promoting the growth and metastasis of gastric cancer [12]. Moreover, it has been discovered by scientists that MIR4435-2HG can boost the expression of downstream genes in the Wnt signaling pathway, including β-catenin, c-Myc, and cyclin D [42]. By reducing the presence of MIR4435-2HG, the Wnt/β-catenin signaling pathway can be deactivated, leading to the inhibition of lung cancer and breast cancer cell proliferation and migration [9,36].…”
Section: Wnt/β-catenin Pathwaymentioning
confidence: 95%
See 1 more Smart Citation
“…Additionally, it has been confirmed through research that MIR4435-2HG has the ability to activate the Wnt/β-catenin signaling pathway by suppressing the expression of desmoplakin (DSP), thus promoting the growth and metastasis of gastric cancer [12]. Moreover, it has been discovered by scientists that MIR4435-2HG can boost the expression of downstream genes in the Wnt signaling pathway, including β-catenin, c-Myc, and cyclin D [42]. By reducing the presence of MIR4435-2HG, the Wnt/β-catenin signaling pathway can be deactivated, leading to the inhibition of lung cancer and breast cancer cell proliferation and migration [9,36].…”
Section: Wnt/β-catenin Pathwaymentioning
confidence: 95%
“…Experimental findings have demonstrated that the suppression of MIR4435-2HG can impede the growth and invasion of glioma cells, thereby hindering the progression of tumors in vivo [41]. Another set of experimental outcomes suggests that MIR4435-2HG can modulate the expression of TAZ by functioning as a sponge for miR-125a-5p, thus fostering the advancement of glioma [42]. Additionally, MIR4435-2HG might also enhance the expression of CD44 by absorbing miR-125a-5p and miR-125b-5p, impacting EMT and the TNF-α signaling pathway [43].…”
Section: Mir4435-2hg and Gliomamentioning
confidence: 99%
“…The expression level of TAZ was upregulated in the brain tissue of glioma patients. Shen et al indicated that the expression of MIR4435-2HG was positively correlated with TAZ expression, while miR-125a-5p expression was negatively correlated with TAZ expression in the brain tissue (Table 1) [61].…”
Section: Glioma Cancermentioning
confidence: 99%